2019
DOI: 10.1039/c9fd90024a
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic approaches to artificial photosynthesis: general discussion

Abstract: Moritz F. Kuehnel opened a discussion of the paper by Andrew I. Cooper: What do you know about the HOMO and LUMO localisation on the polymers? I suppose this is strongly affected by introducing heteroatoms such as sulfur, and that this causes the changes observed when oxidising the thiophene to sulfolane moieties. Can you use different heteroatoms to tweak the redox potentials? Andrew I. Cooper answered: Yesby changing the heteroatom one can change the catalytic activity, but this can also change a variety of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…136 About then, a number of linear poly(phenylene) type polymers had been explored and were found modestly active under UV irradiation (Table 2). 137,138 The field has seen considerable growth in the past few years, 14,15,[139][140][141][142][143][144][145][146][147][148][149] with the pioneering work of Cooper and co-workers who started defining structure-property-activity relationships in the photoactivity of such polymers. As compared to the well-known organic polymers used in photovoltaics, 150 these polymers are typically insoluble.…”
Section: Optoelectronic Engineeringmentioning
confidence: 99%
“…136 About then, a number of linear poly(phenylene) type polymers had been explored and were found modestly active under UV irradiation (Table 2). 137,138 The field has seen considerable growth in the past few years, 14,15,[139][140][141][142][143][144][145][146][147][148][149] with the pioneering work of Cooper and co-workers who started defining structure-property-activity relationships in the photoactivity of such polymers. As compared to the well-known organic polymers used in photovoltaics, 150 these polymers are typically insoluble.…”
Section: Optoelectronic Engineeringmentioning
confidence: 99%
“…Despite a significant uptake of interest in organic materials the exact relationship between their (opto-)electronic/structural properties and the observed hydrogen (HER) and oxygen evolution reaction (OER) rates still remains far from clear. 19 Previously, we demonstrated that empirically the variation in HER/OER rates between polymers can be described in terms of (i) the thermodynamic driving force for proton reduction and water oxidation, controlled by the ionisation potential (IP) and electron affinity (EA) of the neutral polymer, in both the ground state and in the presence of an excited electron-hole pair (exciton), 20,21 (ii) the onset of light absorption and (iii) the dispersability of the polymer particles in suspension. 18,22,23 The dispersability of a polymer probably depends both on the size (distribution) of the polymer particles in suspension and the inherent wettability of the polymer or the sidegroups present.…”
Section: Introductionmentioning
confidence: 99%
“…The faradaic efficiency (FE) for each product was then calculated from the overall charge passed as measured by the potentiostat (Equation (3)), where n is the number of moles of each product calculated through quantitative measurements, Z is the number of moles of electrons required per mole of product, F is the Faraday constant (96485.3 C mol −1 ), and Q is the total charge passed in units of coulombs during each 15 min interval. [ 32,33 ] FE=n×F×ZQ…”
Section: Methodsmentioning
confidence: 99%